ESL teachers' readiness in the teaching and learning of literature / Wilarmy Geniron Jebron - Jebron, Wilarmy Geniron (2011)
Malaysian English teachers are expected to teach not only the English language but also literature in the English as a Second Language (ESL) setting. They are greatly challenged as they are in a setting that needs a lot of enthusiasm and interest. "The use of literary texts in a language class is an important asset to both teacher and learner. For the teacher it can provide additional source for language work. For the learner it can provide interesting language in context" (Compendium, 1989).